A linguagem da moda: uma história de revoluções - da alta costura ao prêt-à-porter (1858-1960) - Cabral, Kenia Moreira (2006)
This work has the intention to show that the history of fashion is made by ruptures or revolutions. The beginning of the fashion field occurs with the birth of the haut couture, and, in a period of hundred years, it will be constituted in a stylistic matrix which is composed by the paradigms of haut couture and prêt-à-porter. Through the analysis of the images, it will be demonstrated that the revolutionary changes in fashion, as a language, reflect the revolutions of the historic context, specifying the social role of the woman. The objective of this work is create a relation between the two biggest paradigm changes which happened in fashion history – the birth of the haute couture in 1858, the ascension of the prêt-à-porter in the end of the fifties – and the feminine social behavior transformations in the same period